“Neurologopedics in theory and practice. Selected aspects of child’s diagnostics and therapy” Published by: Wydawnictwo Naukowe Akademii Techniczno-Humanistycznej, Bielsko-Biała 2012 Scientific edition by: Joanna Skibska, Dawid Larysz - Bartkowiak, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
“Neurologopedics in theory and practice. Selected aspects of child’s diagnostics and therapy” Published by: Wydawnictwo Naukowe Akademii Techniczno-Humanistycznej, Bielsko-Biała 2012 Scientific edition by: Joanna Skibska, Dawid Larysz